(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
The theatre of memory is a significant trend in today’s Spanish drama. The article, after an introduction to the subject, offers a brief analysis of five plays that have the function of filling the holes in the fabric of memory. The principle of our selection was chronological: the five plays – in order of the moments from which the characters recall the events and consequences of the Spanish Civil War – have five perspectives and comprise approximately six decades on the timeline of memory. All the five plays draw the present-day readers’ / spectators’ attention to five moments in history – The Dark Stone to 1937, The 927 Convoy and The Blue Triangle to the years 1940‒1945 remembered from 1965, The Burned Garden and Barefoot under an August Moon to the last moments of the civil war evoked from the late 1970s and the late 1990s respectively – and bring the silenced memories to light from the darkness of oblivion. Key words: The Theater of Memory, Joan Cavallé, Alberto Conejero, Mariano Llorente, Juan Mayorga, Laila Ripoll.